Properties and potential application of efficient biosurfactant produced by Pseudomonas sp. KZ1 strain. Issue 2 (28th January 2019) - Zdarta, Agata; Smułek, Wojciech; Trzcińska, Anna; Cybulski, Zefiryn; Kaczorek, Ewa
Abstract: Increasing use of biosurfactants has stimulated the search for new and efficient biosurfactant-producing bacterial strains, preferably nonpathogenic ones. The aim of the present study was to characterize a new isolated Pseudomonas sp. KZ1 strain and its exocellular surface active compounds. After examining several mineral media of different compositions, the bioreactor-scale production of biosurfactants under optimum conditions was tested. Then, the composition of the isolated biosurfactants was investigated by Fourier-transform infrared spectroscopy and gas chromatography-mass spectrometry analysis and their surface active properties were characterized by adsorption parameters. The results indicated that the Pseudomonas sp. KZ1 biosurfactant had the critical micelle concentration of 0.12 g L −1 and decreased the surface tension decreased to 31.7 mN m −1 . Moreover, the biosurfactant increased the rate of biodegradation of diesel oil by the strains: Pseudomonas sp. KZ1, Pseudomonas sp. OS4 and Achromobacter sp. KW1. The obtained biosurfactant showing attractive properties is a promising and much 'greener' alternative in the application for surfactant-enhanced biodegradation of hydrocarbons.